Perancangan Aplikasi Pengelolaan Pengaduan Masyarakat Pnpm Mandiri Perkotaan Di Provinsi Banten Dengan Metode Waterfall - Arrafi, Abdi; Harsiti, Harsiti (Universitas Serang Raya, 2014)
PNPM Mandiri Perkotaan is a program that seeks substance in poverty reduction through community empowerment concept. Meanwhile, the implementation of a program can not be expected to always run perfectly. For any concerns and complaints from the public related to the implementation of PNPM Mandiri Perkotaan can quickly and appropriately handled. PNPM Mandiri Perkotaan equipped with Complaints Handling (PPM). Complaints management system is done currently perceived not able to meet expectations because the process is still carried out manually using by using common applications such as Microsoft Office Word and Microsoft Office Excel. Thus documenting the complaint has not been done in a fast, accurate, and complete as well as the existing system has not been able to effectively and efficiently in informing the constraints that exist in the field. This study aims to improve the quality of management of public complaints on PNPM Mandiri Perkotaan Banten province so as to resolve the issues related to the management of public reports with the complaints data processing system that is as simple, fast and complete. Steps taken to improve the quality of complaints management as mentioned above, is by way of computerized complaint management to be a readymade system. The designed system will be able to accommodate and manage complaints quickly and appropriately so as to provide information related to obstacles and problems that exist in the field and facilitate the making of a report in accordance with user needs. PPM Application Design using the waterfall method, a method that is able to create a quality system is maintained because the development is structured and supervised. On the other hand this model is a kind of document model is complete, so that the maintenance can be done easily. PPM application is capable of solving the problems associated with the management of public complaints on PNPM Mandiri Perkotaan Banten province to the optimization of complaint management in a fast, accurate, and complete